Penampilan Tiga Genotipa Sawi (Brassica juncea L.) dengan Perbedaan Umur Bibit - Suhartono, Suhartono (Rekayasa, 2008)
The research aims to know the influence of the differences of seed old on growth and yield of three local Chinese mustard (Brassica juncea l.), e.g. Malang, Sidoarjo and Surabaya. The treatments were arranged in randomized block design with three replication.Theresults show that the differences of seed old has significant influence on thegrowth and yield : plant length, leaf number, leaf area, wet weight and dry weight of the plants .. The 25 days of seed old shows the best influence. The influence of three genotipa on the studied parameter is no significant. The differences of seed old interact well with the application of Chinese mustard only on dry weigth of plant.